Shear bond strength of resin composite to silica-based ceramic: a comparative study of different surface treatments - Alqahtani, Abdulaziz; AlHelal, Abdulaziz A.; Almutairi, Mohammed; Alhassoon, Abdulaziz; Alshahrani, Khalid; Alshahrani, Turki; Habib, Syed Rashid (Frontiers in Materials, 2025)
AimThe bond strength between resin composite and ceramics is critical for the success of fractured ceramics repaired with resin composites. The aim of the present study was to investigate and compare the shear bond strength (SBS) between resin composites and lithium disilicate (LD) ceramics using three different surface treatments of the LD.MethodologyOne hundred twenty samples of lithium disilicate were fabricated, out of which 60 were layered with fluoroapatite. Three surface treatment protocols were used: Sandblasting, phosphoric acid and clearfil ceramic prime plus (PA+CFCP); Sandblasting, hydrofluoric acid and clearfil ceramic prime plus (HA+CFCP); Hydrofluoric acid with Monobond N. All specimens were repaired with resin composite, aged using 5,000 cycles of thermocycling (5 °C–55 °C), followed by SBS testing. Specimens were examined under scanning electron and digital microscopes for type of failure. Two-way, one-way ANOVA and t-tests were used for statistical analysis (P < 0.05).ResultsA two-way ANOVA revealed that both ceramic type and the interaction with surface treatment significantly influenced SBS (p < 0.05). While no significant differences in SBS were found among protocols for lithium disilicate, porcelain showed significantly higher SBS when treated with hydrofluoric acid followed by Clearfil Ceramic Primer Plus (HF + CFCP) compared to hydrofluoric acid with Monobond N (HF + MB). Failure mode analysis showed consistent patterns in lithium disilicate across treatments, while porcelain exhibited more mixed failures—indicative of stronger bonds—in the HF + CFCP group. These findings underscore the importance of tailoring surface treatments to the specific ceramic to achieve optimal bond strength and durability.ConclusionClearfil Ceramic Primer Plus demonstrated shear bond strength (SBS) comparable to hydrofluoric acid-based protocols when used with lithium disilicate, even in the absence of hydrofluoric acid. Moreover, in porcelain repair, it achieved superior SBS compared to the conventional hydrofluoric acid and silane combination, highlighting its potential as a safer and more effective surface treatment option for both ceramic types.